2013
DOI: 10.1111/jdi.12122
|View full text |Cite
|
Sign up to set email alerts
|

Potential association between prediabetic conditions and gingival and/or periodontal inflammation

Abstract: Aims/Introduction Prediabetic conditions, which include impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), might be associated with chronic gingival and/or periodontal inflammation. However, the occurrence of this oral inflammation in prediabetic conditions is poorly understood. The present study aimed to assess the association between prediabetes and gingival and/or periodontal inflammation. Materials and Methods A total of 94 Puerto Rican men and women aged 40–65 years, who were residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 42 publications
0
34
0
1
Order By: Relevance
“…Oral conditions, including periodontitis, remain a major public health challenge all over the world, with severe periodontitis affecting 7.4% of the global population (Kassebaum et al., ). There may be an association between prediabetes and gingival and/or periodontal bleeding on gentle probing of the periodontal tissues (Andriankaja & Joshipura, ). Also, self‐reported use of lipid‐lowering agents has shown a potential reduction effect on BOP levels, suggesting a connection between these systemic agents and oral inflammation (Andriankaja et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral conditions, including periodontitis, remain a major public health challenge all over the world, with severe periodontitis affecting 7.4% of the global population (Kassebaum et al., ). There may be an association between prediabetes and gingival and/or periodontal bleeding on gentle probing of the periodontal tissues (Andriankaja & Joshipura, ). Also, self‐reported use of lipid‐lowering agents has shown a potential reduction effect on BOP levels, suggesting a connection between these systemic agents and oral inflammation (Andriankaja et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…). A study of bleeding following probing in individuals who had not received a diagnosis of diabetes revealed that patients above the median bleeding percentage demonstrated an increased likelihood of impaired fasting glucose (odds ratio = 5.5, 95% CI 1.2–25.3) or impaired glucose tolerance (odds ratio 3.6, 95% CI 1.0–13.2; Andriankaja & Joshipura ). In another study, periodontal parameters were assessed in three groups of individuals: (i) pre‐diabetes (defined by FPG or HbA1c), (ii) previously identified pre‐diabetes which was controlled with dietary modification and (iii) normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these studies have been cross-sectional (Andriankaja & Joshipura, 2014; Noack et al, 2000), one used a case-control study design (Javed et al, 2012), and one performed a cross-sectional analysis within a longitudinal study (Cherry-Peppers & Ship, 1993), all of which have been limited by small sample sizes.…”
Section: Introductionmentioning
confidence: 99%